PENGGUNAAN MEDIA GRAFIS UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SDN 008 LUBUK SIAM KECAMATAN SIAK HULU KABUPATEN KAMPAR - Andriani Andriani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is based on the learning result of social sciences of grade VI SD Negeri 008 Lubuk Siam ofKecamatan Siak Hulu which is still very low. This study aims to improve learning outcomes of social sciencesstudents. From the data analysis there is an increase both from teacher activity, student activity, and studentlearning result, that is student activity On cycle I, student activity percentage78,28 (good)% and teacher activitypercentage 92,5% (Very perfect); in cycle II to 86.85% (very good) to 97.5% (very perfect). Judging from the resultsof learning cycle I has increased compared to conventional learning. Early learning outcomes were an average of57.85 (moderate); in cycle I, learning outcomes reached an average of 64.49 or with Enough category; in cycle IIincreased compared to the first cycle to be an average of 78.69 (good). Completeness at first was 6 students(17.16%.); in cycle I 22 students (65,70%); and in cycle II 31 students (88,57%). It can be concluded that graphicmedia enhancement can improve the learning result of Social Sciences of the sixth grade students of SD Negeri 008Lubuk Siam of Kecamatan Siak Hulu.